ميناء فيليب فيل - عسول,صالح (University of Eloued جامعة الوادي, 2023)
يعتبر ميناء فليب فيل أو ميناء سطورة من أهم الموانئ الجزائرية خاصة خلال العهد الاستعماري الفرنسي وهو مرفأ تجاري وميناء لصيد الأسماك ، كما يعد من أقرب الموانئ لمدينة مرسيليا الفرنسية، وازدادت أهميته مع توسع وزيادة انتاج وصادرات المنتجات الزراعية والخامات المعدنية والطاقوية في الجزائر، حيث تم الاعتماد عليه في تصدير المواد الأولية المختلفة، من خلال توظيف مختلف الأرصفة والأسطح المكونة له والتي عرفت توسيعات هامة حسب ما اقتضته ضرورة المصلحة الاقتصادية والتجارية، كما أنه استخدم للتخزين المؤقت لبعض المنتجات الزراعية وغيرها من المنتجات التحويلية كالخمور. واعتمد عليه لتصدير الفحم والقمح الثروات الحيوانية. وكذا المنتجات الزراعية الأخرى. Abstract: Filippeville Port, or Stora Port, is considered one of the most important Algerian ports, especially during the French colonial period. It serves as both a commercial harbor and a fishing port. Additionally, it is one of the closest ports to the French city of Marseille. Its significance has grown in tandem with the expansion and the increased production and export of agricultural, mineral, and energy products in Algeria. It has been relied upon for exporting a lot of raw materials, utilizing its various docks and facilities, which have seen significant expansions to meet economic and commercial demands. Furthermore, it has been used for temporary storage of agricultural products and other transformational products such as wines. The port has played a crucial role in exporting coal, wheat, and livestock, as well as other agricultural products.
دراسة وصفية تاريخية خلال الفترة الاستعمارية
Keywords: حقبة استعمارية فرنسية; فيليب فيل; منتجات زراعية; Port; Filippeville; the French colonial period; TECHNOLOGY::Civil engineering and architecture::Architecture and architectural conservation and restoration; agricultural products; transformational products